(untitled) (Amsterdam, 2005)
Volume 22 of the Fish Physiology Series is entirely devoted to fishes of high latitudes (Arctic and Antarctic). Three central themes comprise the book: The uniqueness of the physiology of fishes that live in cold polar environments, a comparative analysis of physiological patterns exemplified by fishes that live poles apart and, how fishes differ from fishes living in more temperate and tropical habitats. This book highlights the physiological adaptations that evolved to allow certain fish to exploit the frigid, yet productive, Arctic and Antarctic Oceans. The reader will explore what is known, as well as what remains undiscovered, concerning the fish indigenous to both polar regions. This will be of great interest to physiologists, ichthyologists, and comparative biologists researching low temperature biology, fishery scientists, faculty, graduate students * Offers an comparative analysis of the arctic and antarctic polar marine environments * Authors answer the question: What is special about the physiology of fish from the stenothermal Arctic and Antarctic environments? * Includes nine descriptive chapters, 40 tables and over 80 figures
Keywords: Marine fishes,Cá biển; Physiology,Sinh lý học; Polar regions,Vùng cực